Energy transfer studies with perylene bis-diimide derivatives - Icil, H (Marcel Dekker Inc, 1998)
Singlet energy transfer between seven derivatives of perylene diimides and cobalt ions are studied. Energy transfer quenching by cobalt ions is observed for all of the perylene diimides. The rate of bimolecular quenching is found to be about, k(q) congruent to 10(10) M(-1)s(-1), only the N-naphthyl substitution lowered the rates to the range of, k(q) congruent to 10(9) M(-1)s(-1). The critical transfer distances, R-0 (5.8-10.4 A degrees), calculated from donor emission and acceptor absorption spectra, are attributed to a Forster resonance energy transfer process.
Keywords: Dyes